ANALISIS SEMIOTIK ROLAND BARTHES DALAM FILM LAYANGAN PUTUS - Kartini, Kartini (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The Layangan Putus film is a film from the Indonesian web series produced by MD Entertainment which was directed by Benni Setiawan which premiered on November 26, 2021 on We-tv and Inflix. This study aims to find out and understand what are the meanings contained in the film Layangan Putus. Researchers use a descriptive qualitative approach by analyzing, describing and recording the meaning contained in the film using Roland Barthes' theory of semiotic analysis, namely analyzing meaning through three parts, namely the meaning of denotation. , Connotations and Myths, the data used in this study are using primary data and secondary data. Data collection techniques, namely by Documentation, Literature Study and by watching the film Kites breaking up, Analyzing each film scene which contains denotation, connotation and mythical meaning. The results of the research show that the semiotic meaning of Roland Bathes has a very clear meaning in each picture, namely the meaning of denotation, connotation and myth. The meaning of denotation in the analysis includes a tradition of Javanese customs and conflicts in the household and the meaning of connotation contains elements of feelings and opinions. own about the signs that affect feelings and emotions Every relationship between individuals is often seen as an unfriendly quarrel and is often seen as a relationship that is not successful, therefore good communication is needed between families. The mythical meaning in the images that the researcher analyzes is always tied to culture and traditions within the Javanese community in the film Layangan Putus, which is often referred to as the mitoni tradition.